PHYSICAL AND MECHANICAL PROPERTIES OF PETUNG BAMBOO LAMINATE BOARD (Dendrocalamus asper) WITH WIDE TOWARDS BAR ORDER - Febriana Tri Wulandari; Habibi Habibi; Radjali Amin; Raehanayati Raehanayati (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2022)
The use of petung bamboo as a laminated board is expected to save on the use of high quality wood, cost efficiency and is beneficial for forest sustainability so that it can reduce deforestation as little as possible. Bamboo petung can be made of laminated boards because it has thick stem walls (10 mm - 30 mm), thick stem walls will save the use of adhesives. The feasibility of using petung bamboo as a laminated board needs to be tested for its physical and mechanical properties. Physical properties are needed to determine the dimensional stability of the board and mechanical properties are needed to determine the ability of the board to withstand loads. The method used in this research is an experimental method with a non-factorial Completely Randomized Design (CRD). This study aims to determine the physical and mechanical properties of petung bamboo laminated board towards the width. Based on the value of the strength class of the laminated board, the bamboo petung laminated board with the arrangement towards the width is included in the strong class III which can be used as building materials such as door frames, windows, panels, household furniture and wood industries.